Measurements of Radar Backscatter from Arctic Sea Ice in the Summer. - Onstott, R G; Gogineni, S; Delker, C V; Moore, R K (1981)
Measurements of radar backscatter from sea ice located near Svalbarb and Greenland were made during the summer of 1980 as part of Project YMER. These data were acquired using the University of Kansas helicopter-borne microwave active spectrometer (HELOSCAT II) which operated over a frequency range of 8 to 18 GHz and an angle of incidence range of 0 degrees to 50 degrees. The presence of meltponds, the transformation of the snowpack into an ice layer, and the warmer temperatures have contributed to radar signatures that may be significantly different than those observed during the winter and spring. A wide variety of ice conditions were investigated. These included multiyear, thick first-year, thin first-year, young, new, and pressure-ridged ice. The measurement program is described herein. (Author)